PENGELOLAAN LIMBAH ORGANIK SISA BUDIDAYA UNTUK MENINGKATKAN KUALITAS TANAH DI LAHAN CETAK SAWAH DESA BALUNIJUK - Eries Dyah Mustikarini; Tri Lestari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2021)
Balunijuk village is one of the villages in Merawang subdistrict, Bangka Regency which has the potential for rice fields and abundant vegetable products. Agricultural waste is currently not utilized optimally. This community service activity aims to increase the added value of straw agricultural waste and can be used as an alternative fertilizer to increase community agricultural production in Balunijuk Village. The right effort to increase land productivity is to direct the community to process various agricultural waste into compost. The activity was held in Balunjuk village, Merawang District, Bangka Regency, Bangka Belitung Islands province. The service activities carried out through 3 stages of activities, namely compost making training, mole making and product socialization and demonstration activities. Community service activities have presented Gaboktan, village representatives, members of farmer groups and elementary school teachers in Balunijuk Village. The breeding activities that have been carried out include the manufacture of compost and mole products starting with the construction of compost houses, the selection of compost materials, the manufacture of compost and moles and the packaging of solid compost and mole products. Socialization and demonstration activities carried out using the method of presentation and interactive discussion that contains all the questions and positive responses from the guests/audience.